Chapter Il recupero dell'archivio di Gino Cerrito: attività svolte e prospettive di intervento - Boldrini, Enrica (Strumenti per la didattica e la ricerca, 2021)
The contribution illustrates the processing of Gino Cerrito's archive, professor of contemporary history and anarchist militant, and the prospects for its enhancement.